A Review of Congestion Control Techniques in MobileAd-hoc Network - Dhivya, P; Meenakshi, S (International Journal of Computer Sciences and Engineering, 2025)
A mobile ad-hoc network (MANET) is a temporary network that can change locations and configure itself on the fly. MANETs use wireless connections to connect various networks. The mobility and the easy use of mobile devices have motivated researches, to develop MANET protocols to exploit a reliable data transmission facilities provided by the mobile nodes. There are number of issues such as medium access control, routing, resource management, congestion control and power control which affects the reliability of secured communication in MANET. Due to the dynamic network topology, congestion control is an important issue in MANET. Congestion can occur in any intermediate node often due to limitation in resources, when data packets are being transmitted from the source to the destination nodes. The occurrence of congestion results in high data loss, long delay and waste of resource utilization time between mobile nodes. Hence the congestion control technique for detecting and overcoming of congestion is an important research work in MANET. The primary goal of congestion control is the maximum utilization of resources and keeps the load below the capacity. There are several techniques have been proposed for detecting and overcoming congestion in the MANET. This research paper reviews the various proposed congestion control techniques to control congestion in mobile ad-hoc network.